Phytolacca americana var. huadongensis (Phytolaccaceae), a new Chinese variety with thyrsoid inflorescences - Li, Xin-Hua; Yin, Xiao-Ming (Phytotaxa, 2020)
Phytolacca americana var. huadongensis is described and illustrated as a new taxon from eastern China. This new variety differs from P. americana var. americana and var. rigida by the pendulous or arciform thyrsoid inflorescences and infructescences. This new taxon is also morphologically similar to P. sanguinea and P. thyrsiflora, from which can be distinguished by both the pendulous inflorescence (P. sanguinea and P. thyrsiflora have erect thyrsoid inflorescences), and the 10(11)-carpellate gynoecia (vs. 9-carpellate gynoecia in P. sanguinea and 6–9-carpellate gynoecia in P. thyrsiflora).